PRE-SERVICE TEACHERS’ PERCEIVED READINESS IN TEACHING ONLINE IN INTERNATIONAL INTERNSHIP PROGRAM - Tri Yuli Ardiyansah (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2021)
As pre-service teachers, university students in the education faculty are required to take a teaching practice program to deepen their teaching skills. This study focused on finding the pre-service teachers' perceived readiness in teaching online in the international internship program. The writer distributed a survey questionnaire to the pre-service teachers and applied semi-structured interviews to understand the pre-service teachers' perspectives. The finding was described into four indicators: (1) the pre-service teachers were provided with proper equipment and were equipped with good quality of technical skills for teaching online, (2) from the online teaching-learning experiences gained in the university, the pre-service teachers believed that they were confident with their ability for teaching online, (3) regardless some issues in online learning, the pre-service teachers were prepared with some interactive methods to overcome problems that would occur during the process of online learning, and (4) the pre-service teachers committed that they would organize their time management in online learning and provide a meaningful interaction process. The finding concluded that perceived readiness of pre-service teachers in teaching online was considered an essential aspect in the teaching-learning process. Despite many obstacles that could probably occur, the pre-service teachers were fully equipped with proper tools and strategies to provide interactive online learning activities.